KMAD: knowledge-based multiple sequence alignment for intrinsically disordered proteins - Joanna Lange; Lucjan Wyrwicz; Gert Vriend (2015)
Intrinsically disordered proteins (IDPs) lack tertiary structure and thus differ from globular proteins in terms of their sequence-structure-function relations. IDPs have lower sequence conservation, different types of active sites and a different distribution of functionally important regions, which altogether make their multiple sequence alignment (MSA) difficult. The KMAD MSA software has been written specifically for the alignment and annotation of IDPs. It augments the substitution matrix with knowledge about post-translational modifications, functional domains and short linear motifs.MSAs produced with KMAD describe well-conserved features among IDPs, tend to agree well with biological intuition, and are a good basis for designing new experiments to shed light on this large, understudied class of proteins.KMAD web server is accessible at http://www.cmbi.ru.nl/kmad/ A standalone version is freely available.vriend@cmbi.ru.nl.